Farmers’ Knowledge on Agricultural Irrigation Programs: The Case of Altınekin District of Konya Province - Enes Karaman; Mehmet Şahin (Turkish Journal of Agriculture: Food Science and Technology, 2024)
Climate change-induced droughts have various negative impacts on different sectors, especially on agricultural sector. Altınekin District, where the research was conducted, has the lowest precipitation in Konya Province, therefore is expected to be most affected by drought. For sustainable use of water resources, each stage of agricultural production should be carried out within the framework of a specific program. With this study, knowledge level of farmers engaged in irrigated agriculture in Altınekin district regarding irrigation and irrigation programs they applied were determined through a face-to-face survey. Present findings revealed that 38.7% of the participant farmers are aged 50 years and over and a large proportion of them (54.7%) are primary school graduates. Participant farmers were all (100%) using groundwater resources in agricultural production and 88% of them stated that they did not receive any training on irrigation. While 32% of the farmers participating in the survey stated that they had knowledge about the concept of irrigation program, 68% reported that they did not have any knowledge. Incorrect and improper practices regarding efficient use of irrigation water in the region, especially regarding the irrigation program, were identified and solutions were proposed for these problems.